(Re)Searching with Imperial Eyes: Collective Self-Inquiry as a Tool for Transformative Migration Studies - Bass, Madeline J. (2020)
Migration scholars, and the universities and institutions who fund them, at times neglect to address the ways in which the traces of the imperial past, and references to the ‘post’ colonial serve to obfuscate and legitimize discriminatory practices in their work. The ‘imperial eyes’ of the academy set the terms and limitations on interactions, locations, and relationality in research, reducing the agency of migrants, producing stratified configurations in the positionality of both migrants and researchers and, subsequently, exacerbating dynamics of exclusion and extraction. As early-stage researchers, we see a critical need for an approach to migration studies which undermines the ongoing impact of colonialism and the normativity of institutionalized, hierarchical narratives that haunt academia. Our research builds on the work of scholars who write about the autonomy of migration, liberation theorists, and critical Indigenous perspectives, but our positions are also influenced by those on the ‘frontlines’ resisting various manifestations of violence and exclusion. In this article, using an interdisciplinary model, we propose the notion of collective self-inquiry to critically question and inquire into our own methods and approaches and provide a set of methodological tools that can be applied by other researchers within and outside of the university. These tools invite us to work collectively and look more critically at the b/ordering of movement(s) across former empires, thus helping us navigate towards the undercommons, a place where the liberatory potential of the academy can be realized.